A Survey of Communication Partner Training for Individuals with Traumatic Brain Injury in China: Awareness, Benefits, and Barriers - Wei, Guanyu; Keegan, Louise C. (Seminars in Speech and Language, 2025)
Communication partner training (CPT) is an evidence-based treatment approach, applied when working with people with traumatic brain injury (pwTBI). However, all existing programs are available in English only. This article focuses on surveying people in China about their awareness of CPT for pwTBI, and the perceived benefits and challenges of implementing CPT programs, with a view to providing recommendations for optimal services. The authors surveyed 339 medical professional (n = 169) and non-medical professional (n = 170) communication partners to obtain their awareness about CPT. Further, they were asked to identify the potential barriers and benefits of implementing CPT. Potential components that should be considered when developing a CPT program for pwTBI in China were also identified by the communication partners. This article reported low awareness levels about CPT for both medical professional (33.33%) and non-medical professional (22.14%) communication partners. Both groups reported interest in opportunities to receive CPT. The findings of this study will be useful as a guide when developing CPT programs for pwTBI in China. The findings also have implications for the global translation of CPT programs to other languages and countries where they may have a positive impact on the lives of pwTBI and their communication partners.
Keywords: traumatic brain injury; communication partner training; communication difficulties; international issues